2021
DOI: 10.3390/ijerph18084341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fertilizer on Crop Yield and C:N:P Stoichiometry in Arid and Semi-Arid Soil

Abstract: Fertilization can significantly affect the quality of crop and soil. To determine the effects of long-term fertilization on crop yield and carbon:nitrogen:phosphorus (C:N:P) stoichiometry in soil, a study was conducted on the terraced fields of the Loess Plateau from 2007 to 2019. Nine fertilization treatments were included: no fertilizer; organic fertilizer (O); organic and nitrogen fertilizers (ON); organic, nitrogen, and phosphorus fertilizers (ONP); organic and phosphorus fertilizers (OP); phosphorus and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…This indicates that pomelo productivity tends to increase with the increase in the soil quality parameters (SOM, N tot , and P avail ). Similar results were obtained by Sainju et al [ 52 ] and Liu et al [ 53 ], who found significant positive correlation coefficients between soil nutrients (organic carbon, N, and P) and plant yield. An increase in soil BD is known to decrease root penetration and nutrient uptake as well as root formation reduction, which may decrease crop yield [ 54 ].…”
Section: Resultssupporting
confidence: 90%
“…This indicates that pomelo productivity tends to increase with the increase in the soil quality parameters (SOM, N tot , and P avail ). Similar results were obtained by Sainju et al [ 52 ] and Liu et al [ 53 ], who found significant positive correlation coefficients between soil nutrients (organic carbon, N, and P) and plant yield. An increase in soil BD is known to decrease root penetration and nutrient uptake as well as root formation reduction, which may decrease crop yield [ 54 ].…”
Section: Resultssupporting
confidence: 90%
“…on Heavy Metal-Polluted Soil in a Copper Mining Area Fertilizer measures are one of the most important ways to manage crops. The application of fertilizer can not only improve the performance structure of the soil, but also improve the physical and chemical properties of the soil, affecting the absorption and accumulation of heavy metals in the plant roots and thereby increasing the biomass and yield of crops [40]. A study found that while fertilizing crops, fertilizer is not only a fertility factor for crop growth, but also plays a role in the chemical remediation of heavy metalpolluted soil, effectively reducing the effectiveness of heavy metals and reducing the toxicity of heavy metals to plants [41].…”
Section: Effects Of Fertilizer and Arbuscular Mycorrhizal Fungi On Ca...mentioning
confidence: 99%
“…Reforestation and conifer plantations sometimes have to deal with poor, eroded, or degraded soils; it is, therefore, necessary to understand the factors that facilitate the reabsorption of nutrients despite the existence of a shortage or limitation of nutrients [26], which could open interesting perspectives for the articulation of the productive system, and the obtaining of resilient conifers. Soil fertilization and the type of containers used in nurseries have been shown to improve yield and crop quality [27,28]. Future studies should address the different macronutrients present in soils at different depths and their variations in order to understand their relationship with conifer growth and development, which will contribute to sustainable Cunninghamia lanceolata plantations [26].…”
Section: Ecological and Economic Importance Of Conifersmentioning
confidence: 99%